Vitamin D intake in mid-pregnancy and child allergic disease – a prospective study in 44,825 Danish mother-child pairs - Maslova, Ekaterina (BioMed Central, 2013)
BACKGROUND: Past studies suggest that maternal vitamin D intake during pregnancy may protect against child wheeze but studies on asthma are limited. Our objective was to examine the relation between intake of vitamin D in mid-pregnancy and child asthma and allergic rhinitis at 18 months and 7 years. METHODS: We examined data from 44,825 women enrolled during pregnancy in the longitudinal Danish National Birth Cohort (1996–2002). We estimated vitamin D intake from diet and supplements based on information from a validated food frequency questionnaire completed in gestational week 25. At 18 months, we evaluated child asthma using data from phone interviews. We assessed asthma and allergic rhinitis by self-report at age 7 and asthma by using records from national registries. Current asthma at age 7 was defined as lifetime asthma diagnosis and wheeze in the past 12 months. We calculated multivariable risk ratios with 95% CIs comparing highest vs. lowest quintile of vitamin D intake in relation to child allergic disease outcomes. RESULTS: The median (5%-95%ile) intake of total vitamin D was 11.7(3.0-19.4) μg/day (68% from supplements). In multivariable analysis, mothers in the highest (vs. lowest) quintile of total vitamin D intake were less likely to have children classified with current asthma at 7 years (Q5 vs. Q1: 0.74, 95% CI: 0.56, 0.96, P = 0.02) and they were less likely to have children admitted to the hospital due to asthma (Q5 vs. Q1: 0.80, 95% CI: 0.64, 1.00, P = 0.05). We found no associations with child asthma at 18 months or with allergic rhinitis at 7 years. CONCLUSIONS: Our findings suggest a weak inverse relationship between high total vitamin D and asthma outcomes in later, but not early, childhood. The data did not suggest a clear threshold of vitamin D intake above which risk of asthma was reduced.